2015
DOI: 10.1111/dmcn.12687
|View full text |Cite
|
Sign up to set email alerts
|

Visual–perceptual impairment in children with cerebral palsy: a systematic review

Abstract: Aim Visual perception is one of the cognitive functions often impaired in children with cerebral palsy (CP). The aim of this systematic literature review was to assess the frequency of visual–perceptual impairment (VPI) and its relationship with patient characteristics. Method Eligible studies were relevant papers assessing visual perception with five common standardized assessment instruments in children with CP published from January 1990 to August 2011. Results Of the 84 studies selected, 15 were retained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 16 publications
6
88
0
3
Order By: Relevance
“…This pattern of involvement, which mainly comprises parieto‐occipital areas, coincides with previous findings on spastic CP [Ceschin et al, ; Nagae et al, ]. Ceschin et al [] identified several parieto‐occipital nodes with a reduced nodal efficiency, local efficiency and clustering coefficient, and suggested that an altered occipito‐parietal network of disordered connectivity may underlie visuoperceptual dysfunction, an impairment that is estimated to occur in 40–50% of CP cases [Ego et al, ] and that has also been found in our sample (Table ). A possible explanation for the involvement of sensorimotor areas could be related to the high metabolic rate of the primary sensory and motor cortex in the newborn period [Chugani, ; Rennie et al, ] becoming, among other structures, a target region in the event of acute brain asphyxia, which is a common cause of dyskinetic CP [Himmelmann et al, ].…”
Section: Discussionsupporting
confidence: 92%
“…This pattern of involvement, which mainly comprises parieto‐occipital areas, coincides with previous findings on spastic CP [Ceschin et al, ; Nagae et al, ]. Ceschin et al [] identified several parieto‐occipital nodes with a reduced nodal efficiency, local efficiency and clustering coefficient, and suggested that an altered occipito‐parietal network of disordered connectivity may underlie visuoperceptual dysfunction, an impairment that is estimated to occur in 40–50% of CP cases [Ego et al, ] and that has also been found in our sample (Table ). A possible explanation for the involvement of sensorimotor areas could be related to the high metabolic rate of the primary sensory and motor cortex in the newborn period [Chugani, ; Rennie et al, ] becoming, among other structures, a target region in the event of acute brain asphyxia, which is a common cause of dyskinetic CP [Himmelmann et al, ].…”
Section: Discussionsupporting
confidence: 92%
“…Many children with CP have visual-spatial perceptual impairments despite typical or near-typical visual acuity (Akhutina, Foreman, Krichevets, & Vahakuopus, 2003;Ego et al, 2015;Menken, Cermak, & Fisher, 1987;Reed & Drake, 1990;Ortibus, Lagae, Casteels, Demaerel, & Stiers, 2009;Stadskleiv, Jahnsen, Andersen, & von Tetzchner, 2017). Ego et al (2015), in a systematic review of visual-perceptual impairments in children with CP, identified 15 studies which included one of five standardised tests that assessed visual perception.…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
“…Ego et al (2015), in a systematic review of visual-perceptual impairments in children with CP, identified 15 studies which included one of five standardised tests that assessed visual perception. The review indicated that the proportion of children with visual-perception impairments ranged from 40% to 50%, with no study reporting a significant effect of CP subtype or IQ level, although the severity of neurological lesions appeared to be associated with visual perception abilities.…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
See 1 more Smart Citation
“…Top-down disorders, instead, are those of spatial cognition and perception, and are very frequent in CP as well. 22 Our preliminary results, from 15 individuals aged 5 to 23 years, show that head anticipation was lacking in a subgroup of patients and highly variable in the whole sample. Trajectory curvature and variability were significantly higher in spastic diplegia than in controls.…”
Section: Locomotor Trajectories In Cpmentioning
confidence: 69%